THE INFLUENCE OF ATMOSPHERIC ABSORPTION ON VISIBILITY OF GALAXIES - Biernacka, M.; Chudy, M.; Flin, P.; Michniak, M.; Panko, E. (Одеські астрономічні публікації, 2008)
We discuss the influence of atmospheric extinction to visibility of galaxies in the visual region of the spectrum. For this purpose the plates covering the same, small region of the sky taken with 2-m telescope, at different zenith distances were obtained. We investigated the relation between galaxy counts and the zenith distance. We show that the influence of the atmospheric mass to the visibility of galaxies is the same as for stars.